Sistema de gestión para el mejoramiento del talento humano del Colegio Dr. Wilfrido Loor Moreira, Quiroga. - Vélez Tuárez, Mariel Estefanía (2011)
For this research on “Management System to improve Human Talent at Dr. Wilfredo Loor Moreira High school, in the city of Quiroga”, it was analyzed the applicable bibliography as a scientific support when doing the theoretical framework, the methodology and the achieving of the objectives. The situation analysis of Dr. Wilfrido Loor Moreira High school was conducted with the application of data collection, such as interviews to teachers and administrative personnel who work at the institution, as well as surveys to people in Quiroga, parents and senior students, with the purpose of identifying the necessity of preparing an administrative procedure manual to improve the human talent management system in this high school. The results of the surveys and interviews showed the lack of guidelines for a correct management of human talent, there are friendship influences even when hiring the personnel, there is unawareness in some management process of personnel. For everything mentioned above we propose the preparation of the procedure manual highlighting the following recruiting, selection and development processes, updates, and control of personnel in order to improve the performance of human talent according to capacity and qualifications. With all these preceding concerns it is recommend to the authorities and anybody interested to consider in this work the conclusions, recommendations and the application of this manual to achieve successfully all the activities in the institution.